Reconsidering the best minimally invasive approach for patients with herlyn-werner-wunderlich syndrome: Should we push the frontiers for a better outcome? - Moufawad, Graziella; Ayed, Amal; Sleiman, Zaki (Frontiers in Surgery, 2023)
Obstructed hemivagina and ipsilateral renal agenesis (OHVIRA) syndrome is a rare congenital defect of the Mullerian ducts characterized by uterine didelphys, unilateral obstructed hemivagina, and ipsilateral renal agenesis. It frequently presents during puberty, with complications such as pelvic pain, pelvic inflammatory disease and infertility. Surgical management is the mainstay treatment. A vaginal access for septum resection is usually used. However, it can be in difficult in several situations such as a very proximal septum with a small bulge, or in the case of virgin patients with social considerations regarding the hymenal ring integrity. Thus, a laparoscopic approach may be a beneficial alternative. In particular, laparoscopic hemi hysterectomy has recently gained remarkable interest due to its added benefit of treating the cause rather than treating only the symptoms. It removes the source of the bleeding, thus stopping the flow. However, it transforms a bicornuate uterus into a unicornuate uterus, leading to some obstetrical concerns. Should we push the frontiers further and consider laparoscopic hemi hysterectomy for better outcomes as the mainstay management of patients with OHVIRA syndrome?